Geographic Expansion and Banks’ Risk:Evidence from Jordan - Kharabsheh, Buthiena; Daradkah, Demeh (The Arab Journal of Administration, 2019)
This study investigates the impact of geographic expansion on banks’ risk and loan quality in Jordan during the period from 2000 to 2014. Geographic expansion is measured by Shannon Entropy whereby the bank’s risk is measured by standard deviation of ROA, standard deviation of ROE and Z-score. We find evidence that the banking industry in Jordan is highly concentrated and that although banks’ risk decreased with geographic expansion, loan quality was not affected. In addition, the results point to an important issue, that banks in Jordan are only impacted positively by geographic diversification, despite being negatively affected by main economic sector diversification, and are not affected by diversification in the broader sector i.e., service sector. These results are robust using alternative concentration measures and different estimation methods.